Numerical evaluation of the behavior of ordinary and reinforced stone columns. (June 2020) - Nav, Mohebollah Agah; Rahnavard, Rohola; Noorzad, Ali; Napolitano, Rebecca
Abstract: Due to the lack of soil with sufficient load-bearing capacity and the ever-increasing number of large-scale building projects, methods for soil improvement have become vital. Among the conventional methods of soil improvement, the use of reinforced and ordinary stone columns is one of the most prevalent; this is due to its environmental compatibility and proven effectiveness. In this paper, the mechanical behavior of ordinary and reinforced stone columns was studied using ABAQUS, a finite element software. A3D nonlinear finite element model of the column-improved soft soil was built. The results of this work show that while the columns alone decrease the soil settlements, the combination with the geosynthetics additionally augments the effects. Parametric studies were completed to illustrate the effects column grouping on the design process. Thus, the effects of parametric exploration, including inter-column spacing parameters as well as the length and diameter of the stone columns, on the reduction of settlements and bulging were studied for different conditions.